Peran Majelis Taklim terhadap Pembentukan Kesalehan Popular - Abdullah, Muhammad (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
The development of globalization currents is increasingly providing room for understanding Islam which is wrapped in a non-formal education forum for majors. The flexible role of the teaching assembly makes a scholar or preacher can freely develop potentials that can provide good public perception. So, the successful preacher led him to the popular piety that was developed and adapted to the use of technological advances in the form of mass media or print which is growing rapidly.